2017
DOI: 10.1093/dote/dox004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and disease course of patients with esophagogastric junction outflow obstruction

Abstract: Esophagogastric junction outflow obstruction, characterized by preserved peristalsis in conjunction with an elevated integrated relaxation pressure, can result from specific anatomic variants or may represent achalasia in evolution. There is limited information on the clinical significance of this diagnosis. The aim of this study is to describe the clinical characteristics and outcomes in our cohort of patients with esophagogastric junction outflow obstruction.Consecutive adult patients who had undergone high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 12 publications
3
75
2
7
Order By: Relevance
“…In our experience, we observed 2/14 patients with idiopathic EGJOO who were treated with Botox (14%) progress to type 3 achalasia within 20 months of treatment . There have been four patients with EGJOO treated with surgical myotomy who had positive outcomes …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our experience, we observed 2/14 patients with idiopathic EGJOO who were treated with Botox (14%) progress to type 3 achalasia within 20 months of treatment . There have been four patients with EGJOO treated with surgical myotomy who had positive outcomes …”
Section: Discussionmentioning
confidence: 84%
“…Table summarizes all currently published data in regards to EGJOO treatment outcomes . Somewhat surprising are the three reports (Van Hoeij, Perez‐Fernandez and Lynch) suggesting that 44%–52% improve with no therapy …”
Section: Discussionmentioning
confidence: 97%
“…Their conclusion is that performing an EUS in all patients with EGJOO may not be warranted given its low yield at detecting pathology not seen with other less aggressive modalities. Further, Lynch et al reported that in their series of 83 EGJOO cases, 15 patients had either a CT or EUS, none of which revealed any abnormalities; all secondary causes were revealed on BE (paraesophageal hernia, Nissen fundoplication, esophageal stricture, prior laparoscopic band placement, and diverticulum). Finally, DeLay et al reported that in their series of 32 patients with EGJOO, 21 had anatomic abnormalities as potential causes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant advantages that HRM provides compared to conventional manometry is its ability to accurately identify and diagnose the different contractile patterns of aperistalsis seen in achalasia . However, this increased sensitivity has also led to the observation of other manometric abnormalities with unknown clinical significance; one such example is an entity known as esophagogastric junction outflow obstruction (EGJOO) …”
Section: Introductionmentioning
confidence: 99%
“…Proposed etiologies of EGJOO in CCv3 include mechanical obstruction, cardiovascular compression, early achalasia, and potentially hiatal hernia . In addition, outflow obstruction with normal lower esophageal sphincter (LES) function can result from a tight fundoplication wrap or extrinsic compression of the EGJ, such as from a paraesophageal hernia or gastric laparoscopic band placement …”
Section: Introductionmentioning
confidence: 99%